Sivelestat's effect on Candida albicans water‐soluble fraction‐induced vasculitis. Issue 1 (6th May 2022) - Yoshida, Yuya; Banno‐Terada, Rie; Takada, Masashi; Fujii, Toui; Takagaki, Naofumi; Maekawa, Aoi; Tanaka, Arisa; Endo, Miki; Yamada, Ayaka; Mamiya, Ryota; Nagi‐Miura, Noriko; Ohno, Naohito; et al.
Abstract: Background: We investigated the efficacy of sivelestat sodium hydrate (SSH) as a treatment for Kawasaki disease, and its pharmacological action sites, in mice with Candida albicans water‐soluble fraction‐induced vasculitis. Methods: Sivelestat sodium hydrate was administered intraperitoneally to Candida albicans water‐soluble fraction‐induced vasculitis model mice to assess its efficacy in preventing the development of coronary artery lesions based on the degree of inflammatory cell infiltration in the aortic root and coronary arteries (vasculitis score). The pharmacological sites of action were investigated based on changes in neutrophil elastase (NE) and intercellular adhesion molecule 1 (ICAM‐1) positive areas, ICAM‐1 and tumor necrosis factor‐α mRNA expression levels in the upper heart, and the proportion of monocytes in the peripheral blood. Results: The vasculitis score decreased below the lower limit of the 95% confidence interval of untreated mice in 69% of the SSH‐treated mice. The NE‐ and ICAM‐1‐positive regions, and the mRNA expression of ICAM‐1 and tumor necrosis factor‐α were lower in the SSH‐treated mice than in the untreated mice. The proportion of monocytes in the peripheral blood was higher in the SSH‐treated mice than in the untreated mice, whereas monocyte migration to inflammation areas was suppressed in the SSH‐treated mice. Conclusions: Our results showed that SSH might prevent the development of coronary artery lesions and ameliorate disease activity. In addition to its NE‐inhibitory effect, SSH sites of action may also include monocytes.